2008
DOI: 10.1037/1938-8926.1.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Color-blind racial attitudes, social dominance orientation, racial-ethnic group membership and college students' perceptions of campus climate.

Abstract: Racial-ethnic group membership, color-blind racial attitudes (i.e., unawareness of racial privilege, institutional discrimination, and blatant racial issues), and social dominance orientation were used to predict perceptions of campus climate in general and specifically for people of color among a sample of 144 undergraduate, graduate, and professional students at a predominately White university. Results indicate that after controlling for racial-ethnic minority status, perceptions of "general campus climate"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 27 publications
(37 reference statements)
0
109
0
1
Order By: Relevance
“…They have reported feeling left out of diversity initiatives or unsure where they can enter the conversation, and rather than engaging, they tend to opt out (Quaye, 2008). Researchers have worked hard to document the benefits of diversity and have found that white students' participation in diversity-related activities leads to greater openness to and appreciation of diversity and increased awareness of racial privilege (Hurtado 2005;Lopez 2004;Spanierman et al 2008;Worthington et al 2008). Taken together, this research underlines the importance of finding ways to intentionally engage white students in campus diversity efforts, as white students play a critical role in shaping campus climate.…”
Section: The Engaging Diversity Preorientation Programmentioning
confidence: 97%
“…They have reported feeling left out of diversity initiatives or unsure where they can enter the conversation, and rather than engaging, they tend to opt out (Quaye, 2008). Researchers have worked hard to document the benefits of diversity and have found that white students' participation in diversity-related activities leads to greater openness to and appreciation of diversity and increased awareness of racial privilege (Hurtado 2005;Lopez 2004;Spanierman et al 2008;Worthington et al 2008). Taken together, this research underlines the importance of finding ways to intentionally engage white students in campus diversity efforts, as white students play a critical role in shaping campus climate.…”
Section: The Engaging Diversity Preorientation Programmentioning
confidence: 97%
“…Tjitra et al Amerikaans onderzoek bevestigt dat allochtone studenten die zich minder welkom of gesteund voelen op de universiteit, daardoor slechtere academische prestaties leveren en een verhoogde kans op stress en psychologische problemen hebben 17 (iets wat omgekeerd in principe ook voor autochtone studenten zou gelden). Op veel medische faculteiten in Nederland lijken AMS'en ook moeilijker door te stromen naar medische specialismen.…”
Section: Discussieunclassified
“…Additionally, Poteat and Spanierman (2012) found that color-blind racial ideology predicted higher levels of racist ideology and interacted with other predictors of racial bias. Worthington et al (2008) demonstrated that higher levels of color-blindness predicted a more positive rating of general campus climate, suggesting that those who endorse CoBRAs at a higher level will be less likely to recognize hostile environments when they exist. Specifically, Neville et al (2011) found that lower levels of CoBRAs predicted more support for discontinuing the use of a racialized (American Indian) university mascot while higher CoBRA scores predicted a negative reaction to the decision and general support for the use of a stereotyped college mascot.…”
Section: Cobrasmentioning
confidence: 99%
“…The effects of CoBRAs held by counselors (Burkard & Knox, 2004;Neville et al, 2001;Sue et al, 2007;Sue & Sue, 2013), teachers (Atwater, 2008;Wang, Castro, & Cunningham, 2014), college students (Neville et al, 2014;Neville et al, 2011;Poteat & Spanierman, 2012;Worthington et al, 2008), and managers (Offerman et al, 2014) have been explored. Burkard and Knox (2004) found that therapists who demonstrated high levels of CoBRAs were lower on empathy for all clients, had a lower awareness of cultural challenges, and were more likely to assign responsibility for solutions to problems to African American clients than to European American clients.…”
Section: Cobrasmentioning
confidence: 99%